Does a socially well integrated university have anything to do with faculty retention? A study on Kerman University of Medical Sciences-2011. Issue 5 (3rd June 2014) - Amiresmaili, Mohammadreza; Zolala, Farzaneh; Esfandiari, Atefeh; Dehnavieh, Reza; Nekoueimoghadam, Mahmood; Salari, Hedayat; Rakhshan, Amir
Abstract : Purpose: – The purpose of this paper is to measure the relationship between organizational social capital and retention of faculty members in Kerman University of Medical Sciences in 2011. Design/methodology/approach: – Using a stratified multistage sampling, 120 faculty members were recruited to fill the questionnaire. Findings: – There were a direct and positive bilateral ( r =0.65) relationship between social capital and retention of faculty members. Originality/value: – The university officials and policy makers need to pay closer attention to some issues such as providing welfare facilities, salary and wages, benefits, interests and appreciation for faculty members.